Elucidation of the Biotransformation Pathways of a Galnac3-conjugated Antisense Oligonucleotide in Rats and Monkeys - Colby S Shemesh; Rosie Z Yu; Hans J Gaus; Sarah Greenlee; Noah Post; Karsten Schmidt; Michael T Migawa; Punit P Seth; Thomas A Zanardi; Thazha P Prakash; Eric E Swayze; Scott P Henry; et al. (Elsevier, 2016)
Triantennary N-acetyl galactosamine (GalNAc3) is a high-affinity ligand for hepatocyte-specific asialoglycoprotein receptors. Conjugation with GalNAc3 via a trishexylamino (THA)-C6 cluster significantly enhances antisense oligonucleotide (ASO) potency. Herein, the biotransformation, disposition, and elimination of the THA cluster of ION-681257, a GalNAc3-conjugated ASO currently in clinical development, are investigated in rats and monkey. Rats were administered a single subcutaneous dose of 3H-radiolabeled (3H placed in THA) or nonradiolabeled ION-681257. Mass balance included radiometric profiling and metabolite fractionation with characterization by mass spectrometry. GalNAc3-conjugated ASOs were extensively distributed into liver. The THA-C6 triantenerrary GalNAc3 conjugate at the 5'-end of the ASO was rapidly metabolized and excreted with 25.67 ± 1.635% and 71.66 ± 4.17% of radioactivity recovered in urine and feces within 48 hours postdose. Unchanged drug, short-mer ASOs, and linker metabolites were detected in urine. Collectively, 14 novel linker associated metabolites were discovered including oxidation at each branching arm, initially by monooxidation at the β-position followed by dioxidation at the α-arm, and lastly, tri and tetra oxidations on the two remaining β-arms. Metabolites in bile and feces were identical to urine except for oxidized linear and cyclic linker metabolites. Enzymatic reaction phenotyping confirmed involvement of N-acetyl-β-glucosaminidase, deoxyribonuclease II, alkaline phosphatase, and alcohol + aldehyde dehydrogenases on the complex metabolism pathway for THA supplementing in vivo findings. Lastly, excreta from monkeys treated with ION-681257 revealed the identical series as observed in rat. In summary, our findings provide an improved understanding of GalNAc3-conjugated-ASO metabolism pathways which facilitate similar development programs.